Analisis Yuridis Terhadap Kedudukan Barang Bukti Dalam Tindak Pidana Perikanan Mengenai Alat Tangkap Kaitannya Dengan Pelaksanaan Tugas Kejaksaan Dalam Penuntutan - Arpan Carles Pandiangan; Alvi Syahrin; Suhaidi Suhaidi; Edi Yunara (Universitas Sumatera Utara, 2019)
Abstract. Its law enforcement still has weakness concerning the proving exhibit evidence in a court about catching equipment in fishery criminal act. It can be seen from the Ruling No. 2064 K/Pid.Sus/2016 which does not realize agreement in law. The research problems are how about the regulation on exhibit evidence in a court confiscated from fishery criminal act in Indonesia, how about its position related to the prosecutors’ job, and how about judges’ consideration in the Supreme Court on the exhibit evidence. Concerning the exhibit evidence, Article 76A of Law on Fishery reads, ‘that the exhibit evidence in fishery criminal act can be confiscated for the State and terminated based on the approval of the Head of District Court. Concerning catching equipment, the prosecutor has the authority to confiscate the exhibit evidence for evidence in the court as it is stipulated in Article 42 of HIR. Concerning the Ruling No. 2064 K/Pid.Sus/2016, it can be said that the termination and the confiscation of catching equipment in judges’ decision is not in accordance with the agreement in law: the principles of justice, certainty, and benefit since the little fishermen are harmed since they have lost their livelihood. It is recommended that people’s welfare approach be done. It needs explanation about the position of exhibit evidence (catching equipment) so that fishermen will not be harmed. Besides that, the prosecutors’ authority should be improved in law on fishery concerning prosecution on exhibit evidence in the fishery criminal act. Keywords: fishery criminal act, exhibit evidence, the supreme court’s ruling